Review of MORENO VERGARI, ed., with the contributions of AHMEDSAAD MOHAMMED OMER, GIORGIO BANTI, GIANNI DORE, MORENO VERGARI, and ROBERTA VERGARI, Housing and Dwelling Among the Saho-speaking Communities of Eritrea and Ethiopia: History, Anthropology and Lexicography - Saleh Mohammad, Abdulkader (Aethiopica, 2024)
Book review